Endoscopic Resection of Ampullary Tumours: Long-term Outcomes and Adverse Events. Issue 1 (18th March 2019) - Alali, Ali; Espino, Alberto; Moris, Maria; Martel, Myriam; Schwartz, Ingrid; Cirocco, Maria; Streutker, Catherine; Mosko, Jeffrey; Kortan, Paul; Barkun, Alan; May, Gary R
Abstract: Background: The management of ampullary lesions has shifted from surgical approach to endoscopic resection. Previous reports were limited by small numbers of patients and short follow-up. The aim of this study is to describe short- and long-term outcomes in a large cohort of patients undergoing endoscopic ampullectomy. Methods: Retrospective study of endoscopic ampullectomies performed at a tertiary center from January 1999 to October 2016. Information recorded includes patient demographics, clinical outcomes, lesion pathology, procedural events, adverse events and follow-up data. Results: Overall, 103 patients underwent endoscopic resection of ampullary tumours (mean age 62.3 ± 14.3 years, 50.5% female, mean lesion size 20.9 mm; 94.9% adenomas, with a majority of lesions exhibiting low-grade dysplasia (72.7%). Complete endoscopic resection was achieved in 82.5% at initial procedure. Final complete endoscopic resection was achieved in all patients with benign pathology on follow-up procedures. Final pathology showed that 11% had previously undiagnosed invasive carcinoma. Delayed postprocedure bleeding occurred in 21.4%, all of which were managed successfully at endoscopy. Acute pancreatitis complicated 15.5% of procedures (mild in 93.8%). Perforation occurred in 5.8%, all treated conservatively except for one patient requiring surgery. Piecemeal resection was associated with significantly higher recurrence compared to en-bloc resection (54.3% versus 26.2%, respectively, P = 0.012). All recurrences were treated endoscopically. Conclusion: Endoscopic ampullectomy appears both safe and effective in managing patients with ampullary tumours in experienced hands. Most adverse events can be managed conservatively. Many patients develop recurrence during long-term follow-up but can be managed endoscopically. Recurrence rates may be reduced by performing initial en-bloc resection.